Maraknya Online Shop Terhadap Perubahan Gaya Hidup Konsumtif Perempuan - Evianah Evianah; Dwi Indah Mustikorini (Forum Manajemen, 2023)
The purpose of this study, firstly, is to analyze the rise of online shops for changes in women's consumptive lifestyle, secondly, to find out what factors cause UWKS FE students to make purchases through online shops, and thirdly, to find out the impact of online shopping. shop towards changes in the consumptive lifestyle of women in FE UWKS students. The results of this study indicate that there is a change in consumptive behavior of students at Wijaya Kusuma University Surabaya, especially female students of the Faculty of Economics and Business. These changes include changes in the way of shopping which was originally conventional, such as having to come to malls, or offline shops, now to move to online shops.Another factor that can cause them to shop through online shops is the ease factor in accessing media that offers products in the online shop so that they become more consumptive. In addition, it is also caused by several factors, including time efficiency factors, as fulfillment of needs, supportive and easy access, influence from the peer environment, and the prices offered in digital marketing are very competitive, especially if the online store is a marketplace. In the marketplace the prices offered are very competitive, many shops compete in providing prices.